Male Sterility of an AHAS-Mutant Induced by Tribenuron-Methyl Solution Correlated With the Decrease of AHAS Activity in Brassica napus L. - Lv, Jinyang; Huang, Qianxin; Sun, Yanyan; Qu, Gaoping; Guo, Yuan; Zhang, Xiaojuan; Zhao, Huixian; Hu, Shengwu (Frontiers in Plant Science, 2018)
Tribenuron-methyl (TBM), an acetohydroxyacid synthase (AHAS)-inhibiting herbicide, can be used as an efficient chemical hybridization agent to induce male sterility for practical utilization of heterosis in rapeseed (Brassica napus L.). Utilization of rapeseed mutants harboring herbicide-resistant AHAS alleles as the male parent can simplify the hybrid seed production protocol. Here we characterized a novel TBM-resistant mutant K5 derived from an elite rapeseed variety, Zhongshuang No.9 (ZS9), by ethyl methyl sulfonate mutagenesis. Comparative analysis of three BnAHAS genes (BnAHAS1, BnAHAS2, and BnAHAS3) between the mutant K5 and ZS9 identified a C-to-T transition at 544 from the translation start site in BnAHAS1 in K5 (This resistant allele is referred to as BnAHAS1544T), which resulted in a substitution of proline with serine at 182 in BnAHAS1. Both ZS9 and K5 plants could be induced complete male sterility under TBM treatment (with 0.10 and 20 mg•L-1 of TBM, respectively). The relationship between TBM-induced male sterility (Y) and the relative AHAS activity of inflorescences (X) could be described as a modified logistic function, Y=100-A/(1+Be(-KX)) for the both genotypes, although the obtained constants A, B, and K were different in the functions of ZS9 and K5. Transgenic Arabidopsis plants expressing BnAHAS1544T exhibited a higher TBM resistance of male reproductive organ than wild type, which confirmed that the Pro-182-Ser substitution in BnAHAS1 was responsible for higher TBM-resistance of male reproductive organs. Taken together, our findings provide a novel valuable rapeseed mutant for hybrid breeding by chemical hybridization agents and support the hypothesis that AHAS should be the target of the AHAS-inhibiting herbicide TBM when it is used as chemical hybridization agent in rapeseed.